Deep basin temperature and heat-flow field in Denmark – New insights from borehole analysis and 3D geothermal modelling. (January 2020) - Fuchs, Sven; Balling, Niels; Mathiesen, Anders
Highlights: This paper presents a 3D numerical temperature and heat-flow study of Danish onshore areas including deep sedimentary basins. We present 21 new heat-flow values with significant variation according to regional structural and tectonic background. Most of Denmark provides suitable conditions for low enthalpy geothermal utilization; local potential for electricity production. A spatial variable thermal parameterization excels the homogeneous approach in terms of temperature prediction accuracy. Abstract: We present a 3D numerical crustal temperature model with inverse optimisation methodology and analyse the present-day conductive thermal field of the Danish onshore subsurface. The model is based on a comprehensive analysis and interpretation of borehole and well-log data for thermal and petrophysical rock properties and their regional variability and spatial distribution across the country. New values of terrestrial surface heat flow derived from 21 deep well locations are 65–76 mW m −2 (mean: 72 ± 3) for the Danish Basin, 77–86 (81 ± 5) for the Danish part of the North German Basin, and 61–63 (62 ± 1) for the Sorgenfrei-Tornquist-Zone/Skagerrak-Kattegat Platform, respectively. The observed heat flow variations are consistent with the position of the Danish area in the transition zone between the old Precambrian Baltic Shield (low heat flow) and central European accreted terrains and deep basin systems (significantly higher heat flow). For the temperature modelling, conductivities and heat flow are constrained and validated (rms: 1.2 °C, ame: 0.7 °C) by borehole temperature data covering a depth range of up to 5 km (137 values from 46 wells). Significant modelled temperature variations are caused by (i) complex geological structures (thickness variations, salt structures) and (ii) the variation of rock thermal conductivity between and within geological formations as well as lateral variation in background heat flow. Modelled temperature for major geothermal reservoirs indicate substantial potential for low enthalpy heating purposes. Reservoir temperatures above 130 °C, of interest for the production of electricity, are observed for some local areas, however, likely, too deep for non-stimulated sufficient reservoir quality.